"Blockchain‐Like" MIL‐101(Cr)/Carbon Black Electrodes for Unprecedented Defluorination by Capacitive Deionization (Small 10/2023). Issue 10 (10th March 2023) - Yu, Fei; Zhang, Xiaochen; Liu, Peng; Chen, Bingbing; Ma, Jie
Abstract : "Blockchain‐Like" Interface Moderation Method Carbon black as a "chain" to guide the charge transfer effectively promotes the F‐ transfer into the metal‐organic framework (MOF), and through the redox reaction stored in the MOF "block". This interface moderation method effectively improves the fluoride removal performance of the MOF electrode. More details can be found in article number 2205619 by Jie Ma and co‐workers.